Highly Sensitive Determination of Bisphenol A in Bottled Water Samples by HPLC after Its Extraction by a Novel Th-MOF Pipette-Tip Micro-SPE. (26th December 2019) - Kaykhaii, Massoud; Yavari, Eilnaz; Sargazi, Ghasem; Ebrahimi, Ahmad Khajeh
Abstract: In this study, a novel thorium metal organic framework was synthesized, characterized and used as a sorbent for very efficient pipette tip micro solid-phase extraction of bisphenol A in bottled drinking water samples using high-performance liquid chromatography as detecting instrument. Parameters which influence extraction efficiency such as pH, sample volume, amount of sorbent, type and volume of eluent, number of aspirating and dispensing cycles for extraction and elution, and volume of the sample solution were studied and optimized. A linear calibration curve was obtained in the range of 0.002–0.456 ng mL −1 ( r 2  = 0.996) with a detection limit of 0.0010 ng mL −1 . Repeatability of batch-to-batch extraction was better than 5.0% and a reproducibility of 3.2% for real samples obtained.